2023
DOI: 10.7554/elife.85142
|View full text |Cite
|
Sign up to set email alerts
|

The large GTPase Sey1/atlastin mediates lipid droplet- and FadL-dependent intracellular fatty acid metabolism of Legionella pneumophila

Abstract: The amoeba-resistant bacterium Legionella pneumophila causes Legionnaires' disease and employs a type IV secretion system (T4SS) to replicate in the unique, ER-associated Legionella-containing vacuole (LCV). The large fusion GTPase Sey1/atlastin is implicated in ER dynamics, ER-derived lipid droplet (LD) formation, and LCV maturation. Here we employ cryo-electron tomography, confocal microscopy, proteomics, and isotopologue profiling to analyze LCV-LDs interactions in the genetically tractable amoeba Dictyoste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…pneumophila also utilize fatty acids and/or complex lipids for intracellular growth, as demonstrated by fluorescent labelling of bacteria when infected macrophages were fed fluorophore-conjugated fatty acids ( Fig 4E ) and, in the amoebae Dictyostelium discoideum , incorporation of 13 C into L . pneumophila when infected amoeba were supplemented with [ 13 C]palmitate [ 45 ]. Additionally, Hilbi and colleagues demonstrated that a L .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…pneumophila also utilize fatty acids and/or complex lipids for intracellular growth, as demonstrated by fluorescent labelling of bacteria when infected macrophages were fed fluorophore-conjugated fatty acids ( Fig 4E ) and, in the amoebae Dictyostelium discoideum , incorporation of 13 C into L . pneumophila when infected amoeba were supplemented with [ 13 C]palmitate [ 45 ]. Additionally, Hilbi and colleagues demonstrated that a L .…”
Section: Discussionmentioning
confidence: 99%
“…pneumophila mutant lacking a homolog of fadL , which encodes a fatty acid import protein, accumulated less 13 C-containing molecules and grew more poorly in D . discoideum [ 45 ]. Finally, Legionella gormanii membranes were recently shown to surprisingly contain the sphingolipid ceramide, implicating host-derived fatty acid-containing molecules in performing a structural role in the bacterium as well [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations